Coexistence of β-Lactamases in Community-Acquired Infections in a Tertiary Care Hospital in India. (11th December 2019) - Mirza, Shahzad; Jadhav, Savita; Misra, R. N.; Das, Nikunja Kumar
Abstract : Introduction . The trends of β -lactamases producing Enterobacteriaceae is ever increasing, and limited studies have reported investigating coexistence of β lactamases in Enterobacteriaceae . A cross-sectional study after approval from the Institutional Ethical committee was conducted between June 2014 and May 2016 in community-acquired infections due to multidrug-resistant organisms in our tertiary care. Nonrepetitive clinical samples from the out-patient department (OPD) were processed for bacteriological culture and identification of Enterobacteriaceae. An antibiotic susceptibility test, screening, and phenotypic confirmation for ESBLs and carbapenemases and AmpC producers were performed to check for coexistence of these enzymes. Results . Nonrepetitive clinical specimens processed for culture and identification in our hospital revealed 417 positive isolates in community acquired infections which were multidrug-resistant organisms, and on screening for β -lactamases, 293 isolates were positive for one of the three beta lactamases, ESBL, AmpC, or carbapnemases. Coproduction of ESBL and MBL was seen in 5 isolates, 35 isolates showed coproduction of ESBL and AmpC enzymes, and AmpC and MBL coproduction was exhibited in only in 5 isolates. Conclusions . Coexistence of ESBLs, AmpC producers, and carbapenemases has been described. Continuous monitoring and surveillance and proper infection control and prevention practices will limit the further spread of these superbugs within the hospital and beyond.